L’INCIDENCE DES NAUSEES ET VOMISSEMENTS CHIMIO-INDUITS (DANS LE SERVICE D’ONCOLOGIE de l’EPH DE KASR EL-HIRENE) - Mohguen Yasser; Zekaik Abderrahman; Abi Achour Essadek Riad (université ammar telidji laghouat, 2024)
Incidence of chemotherapy-induced nausea and vomiting Prospective study at Kasr El Hiran hospital in Laghouat (Professor Benlahrech Zakia Al-Batoul) Objective: To study the incidence of chemotherapy-induced nausea and vomiting (CINV), determine if the prescriptions in our department comply with the recommendations of expert societies, and evaluate the influence of certain patient- specific factors on the occurrence of CINV. Materials and Methods: This is a prospective observational study conducted at the day hospital of the medical oncology service at EPH Kasr El Hiran Laghouat, spanning a period of 06 months from october 2023 to Marsr 2024 Results: At the end of this study, 56 women and 35 men were interviewed, with a mean age of 57,12 years. Breast cancer was the most frequent underlying neoplastic pathology (40,7%). The majority of chemotherapy protocols used were classified as low emetic risk (45,5%). The incidence of CINV was 85,71%, of which 57,70% occurred in the acute phase. According to our results, none of the risk factors appear to have an influence on the incidence of CINV, except of medical history of CINV of the patient and the prescriptions are not in compliance with the recommendations of expert societies. Conclusion: Our results indicate that the management of CINV remains overall unsatisfactory and could be improved by providing increased accessibility to aprepitant.
cd-rom